Price relationships along the Norwegian salmon value chains: A comparative study of the leading consumption market in France and the largest processing industry in Poland - Miranda Svanidze; Guðrún Ólafsdóttir; Ivan urić; Maitri Thakur (Aquaculture Economics & Management, 2023)
This study investigates price relationships along the Norwegian salmon value chains in France, the EU's leading consumption market for salmon, and Poland, the EU's largest “processing hub.” Using a vector error correction model framework, our results indicate that the salmon price determination is a supplier-driven process, with the export prices in Norway influencing prices in France and Poland, but not vice versa. Results also suggest that price linkages are strong between the export market in Norway and the retail market in France and the processing industry in Poland; however, the Polish retail sector is separated from markets at the upstream level, while price discovery at the French wholesale market is dominated by the retail market. Our findings imply that the evolved market structures lead to efficiently functioning retail markets in France and wholesale markets in Poland, but put the French wholesale and Polish retail markets at a disadvantage.
Keywords: 330; Atlantic salmon; France; Norway; Poland; price transmission; value chain